An integrated biorefinery to produce 5-(hydroxymethyl)furfural and alternative fuel precursors from macroalgae and spent coffee grounds. Issue 23 (10th November 2021) - Pereira, André Prates; Woodman, Timothy J.; Chuck, Christopher J.
Abstract : In this study an integrated biorefinery is presented, producing 5-hydroxymethylfurfural (HMF) and products from the hydrothermal liquefaction of spent coffee grounds blended with macroalgae. Abstract : 5-Hydroxymethylfurfural (HMF) is a promising platform chemical produced from the dehydration of C6 sugars, that is a precursor for a range of renewable fuels and polymers. In this study, an integrated macroalgal biorefinery was designed to produce an array of products including HMF, hydrothermal liquefaction (HTL) biocrude and biochar. In this process two different species of macroalgae, Ulva lactuca and Chorda filum, were investigated and co-processed with spent coffee grounds to assess if such blends could be effectively used, with the spent coffee grounds mitigating for lower macroalgae availability throughout the year. U. lactuca and the spent coffee ground blends were effectively used in a biorefinery design for the production of HMF. Interestingly, blends yielded higher amounts of HMF (35–47 g per kg of dry biomass processed) than the separate components alone. This is presumably due to the elevated amount of C6 sugars being available from the macroalgae, coupled with the presence of lipids from the coffee grounds. The lipids likely form a separate organic layer in the dehydration reaction, into which the HMF migrates after being formed in the aqueous fraction, halting further dehydration reactions to levulinic acid. The HTL on the resultant solids from dehydration yielded a relatively similar amount of biocrude (68–78 g per kg of dry biomass) compared to spent coffee grounds (SCG) (90 g per kg of dry biomass). However, the C. filum biorefinery yielded far lower biocrude and HMF, presumably due to the lower lipid and C6 sugar content in this feedstock. Overall, an HMF biorefinery from macroalgae is plausible, with spent coffee grounds being a highly suitable material to make up for seasonal availability. However, the large difference in yields from macroalgal species demonstrates the importance of high lipid content, alongside higher C6 sugar composition, in the macroalgal feedstock.